Challenges and Opportunities for Christian Religious Education in the Development of Information Technology in Class IX - Rahani Rahani; Karolina Karolina; Dwi Sartica; Urbanus Urbanus (EDUJAVARE: International Journal of Educational Research, 2026)
The rapid development of information technology has transformed almost every aspect of human life, including the educational sector. This study aims to analyze the challenges and opportunities of Christian Religious Education (CRE) in the development of information technology and to examine how teachers optimize technology integration in learning among Grade IX students at SMP Negeri 8 Palangka Raya. The study employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings reveal that the major challenges faced by Christian Religious Education include students’ excessive use of digital devices, exposure to online content that may contradict Christian values, disparities in teachers’ digital competencies, and limitations in technological infrastructure. Despite these challenges, information technology provides significant opportunities to enhance access to religious learning resources, improve student engagement through interactive multimedia, facilitate collaborative learning, and support spiritual formation through digital faith-based platforms. The study also found that teachers optimize technology use by integrating multimedia resources into instruction, utilizing digital communication platforms, promoting digital literacy and ethical technology use, and continuously improving their technological and pedagogical competencies. The study concludes that the effective implementation of Christian Religious Education in the digital era requires a balanced approach that embraces technological innovation while maintaining the core mission of nurturing students’ faith, character, moral values, and spiritual development.